Exclusive Breastfeeding With Stunting - Umiyah, Astik; Hamidiyah, Azizatul (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Indonesia ranks the 5th most stunting in the world. Stunting has long-term impacts both individually and socially, including reduced cognitive & physical development, lower productivity, and increased risk of degenerative diseases such as diabetes. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddler in the Banyuputih Health Center, Situbondo Regency. This research was a quantitative study with a cross-sectional design. The sample in the study was 274 toddlers in the Banyuputih Health Center working area. The sampling technique used was proportional random sampling. This research instrument used an observation sheet. The results showed that exclusive breastfeeding (Pvalue 0.025) was associated with the incidence of stunting. From the OR value, it was obtained 2.451, meaning that children who did not receive exclusive breastfeeding had a chance to become stunted 2.451 times compared to children who received exclusive breastfeeding.